HUBUNGAN AKTIVITAS FISIK DAN RIWAYAT GENETIK DENGAN KADAR ASAM URAT DI POSYANDU CINTA LANSIA - Nurul Magfira; Hariza Adnani (Jurnal Ilmu Keperawatan dan Kebidanan, 2021)
Adding age causes some changes both physically and mentally. These changes affect a person's condition both psychological, physiological, and socio-economic aspects and experience various complaints and health problems such as increased uric acid levels in the blood (hyperuricemia).  This study aims to determine the relationship between physical activity and genetic history with uric acid levels at the Cinta Lansia Banguntapan Bantul posyandu. The research design was a survey analysis with a case control study design. The research sample was 34 elderly using purposive sampling. Collecting data using the PAL form and data analysis using the Chi - Square test. The results of this study showed that those corelated with gout in the elderly were physical activity (P value = 0.007, OR = 15.00) and genetic history (P value = 0.004, OR = 10.714).  It is recommended for elderly posyandu cadres to improve the elderly exercise program and strive for health promotion in the community related to gout and its prevention.